Ionizing and Non-Ionizing Radiation 2020
DOI: 10.5772/intechopen.85115
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Radiation: Natural Radioactivity Monitoring

Abstract: People are continuously exposed to ionizing radiation from many sources, including natural radioactive substances that are produced in the atmosphere and on Earth, in addition to radionuclides manufactured for various applications. Exposures vary among different places depending on many parameters. There are regions with considerably high natural background radiation while most places classified as low to medium levels. This noticeable interest pronounced worldwide is radioactivity monitoring and wide surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Environmental radiation studies are carried out by monitors, nuclear spectroscopy, radon measurements, and geological surveys to quantify the levels of natural radiation levels [19,[22][23][24][25]. The information obtained from these studies often is reported as maps; the values of the radiation levels and dose gradients are crucial for assessing potential health risks, establishing radiation protection guidelines, and developing strategies for managing areas with elevated natural radioactivity [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental radiation studies are carried out by monitors, nuclear spectroscopy, radon measurements, and geological surveys to quantify the levels of natural radiation levels [19,[22][23][24][25]. The information obtained from these studies often is reported as maps; the values of the radiation levels and dose gradients are crucial for assessing potential health risks, establishing radiation protection guidelines, and developing strategies for managing areas with elevated natural radioactivity [26][27][28].…”
Section: Introductionmentioning
confidence: 99%